From Replacement to Symbiosis: A Grounded Theory Study on AI-Assisted Teaching Models in Secondary School History Classrooms - Li, Ying; Liao, Nian (Innovative Applications of AI, 2025)
This study analyzes and explores AI-assisted teaching models in secondary school history classrooms through observations of teaching activities. The research findings reveal a significant evolution in AI’s role in history teaching, transitioning from a "replacement" phase to a "symbiosis" phase. In the "replacement" phase, AI primarily undertakes foundational tasks such as chronological ordering and historical data classification. While AI significantly enhances classroom efficiency in this stage, it fails to effectively stimulate students’ deep thinking and critical analysis. With technological advancements and evolving educational philosophies, AI in the "symbiosis" phase begins to function as a "critical interlocutor," presenting diverse historical perspectives, fostering students’ critical thinking, and forming an interactive synergy among teachers, students, and AI. The study identifies core dimensions of AI-assisted teaching, including historical data processing collaboration and spatiotemporal concept construction collaboration. These dimensions reflect how teachers, with technological support, guide students toward deep learning and critical inquiry.